96 Late-Breaking: Effects of graded amounts of Leucine in milk replacer on neonatal calf growth and nutrient digestibility. (7th December 2018) - Reiners, J; Carlin, K; Vonnahme, K; Steele, M; Swanson, K
Abstract: Production of cattle can be limited by inadequate neonatal amino acid nutrition. Previous data suggests that select amino acids are important precursors for protein synthesis, and could potentially be increased in neonates. Leucine is known to stimulate mTOR activity and insulin secretion in neonatal pigs, and is the most potent amino acid for stimulating protein synthesis. We evaluated the effects of amounts of leucine in milk replacer on neonatal calf growth and nutrient digestibility. Twenty-four calves (43.25 ± 1.16 kg) were sorted to 4 levels of leucine supplementation (0, 0.4, 0.6, and 0.8 g/kg BW) and blocked by treatment start date. Calves were housed individually and fed milk replacer with supplemental leucine for 29 days. Total feces and urine were collected from day 22–29 to measure nutrient digestibility and N balance. Data were analyzed using the general linear model of SAS as a randomized complete block design. Treatment had no effect (P = 0.85) on calf weight throughout the experiment. There was a linear increase in CP (P < 0.001) and N (P < 0.001) intake as leucine inclusion increased. There were no effects of treatment on digestibility of N (P=0.63), CP (P=0.59), OM (P=0.51), DM (P=0.49), or ash (P=0.22). Weight of omasum decreased when supplementation of leucine was at 0.4, but increased when supplementation was at 0.6 or greater (P < 0.001); pancreas weight increased linearly (P=0.03), and spleen weight tended to increase (P=0.08) with increased supplementation of leucine. Results indicate that increasing leucine supply to neonatal calves does not influence growth or nutrient digestibility. However, the effects of leucine supplementation did influence omasum, pancreas, and spleen weights. This work is supported by Animal Health and Production and Animal Products Accession No. 101206 from the USDA National Institute of Food and Agriculture.